Evening wear of blue-blocking glasses for sleep and mood disorders: a systematic review. (3rd October 2021) - Hester, Landon; Dang, Deanna; Barker, Christopher J; Heath, Michael; Mesiya, Sidra; Tienabeso, Tekenari; Watson, Kevin
ABSTRACT: Blue-blocking glasses, also known as amber glasses, are plastic glasses that primarily block blue light. Blue-blocking glasses have been studied as a sleep intervention for insomnia, delayed sleep-phase disorder, shift work, jet lag, and nonpathologic sleep improvement. Blue-blocking glasses have also been studied as a treatment for bipolar disorder, major depression, and postpartum depression. Blue-blocking glasses improve sleep by inducing dim-light melatonin onset by reducing activation of intrinsically photosensitive retinal ganglion cells (ipRGCs) which are most sensitive to blue light and are a major input for circadian regulation; their mechanism for mood regulation is unclear but may be similar to that of dark therapy for bipolar disorder where patients are kept in darkness for an extended period every night. A systematic search of the scientific literature identified a total of 29 experimental publications involving evening wear of blue-blocking glasses for sleep or mood disorders. These consisted of 16 randomized controlled trials (RCTs) published in journals with a total of 453 patients, 5 uncontrolled trials, 1 case series, 1 case study, and 6 abstracts from conference proceedings. Only 1 case study and 1 RCT were for acutely manic patients but both found substantial decreases in manic symptoms with the use of blue-blocking glasses; these give preliminary clinical evidence of efficacy that makes blue-blocking glasses a high-yield intervention to study for bipolar disorder. Findings in the 3 publications for major depression and postpartum depression were heterogeneous and conflicting as to their efficacy. Out of the 24 publications focusing on sleep, there was substantial evidence for blue-blocking glasses being a successful intervention for reducing sleep onset latency in patients with sleep disorders, jet lag, or variable shift work schedules. Given the well-established biological mechanism and clinical research showing that blue-blocking glasses are effective for inducing sleep, they are a viable intervention to recommend to patients with insomnia or a delayed sleep phase.